Pengaruh Budaya Organisasi Dan Etos Kerja Terhadap Kepuasan Kerja Berdampak Pada Kinerja Tenaga Pendidik Di Politeknik KODIKLATAD - Setiawan, Arif; Sawitri, Dyah (Fakultas Ekonomi Universitas Wisnuwardhana, 2019)
Kodiklatad Polytechnic is one of the educational institutions in the Kodiklat TNI AD that conducts science and technology education. The education system applied in this institution is a combination of the education system that applies in the Army and the educational system that applies in the higher education environment. The application of the Basic Tri Pattern of Education remains valid and is integrated with the semester credit system that is commonly applicable in universities. The output of this education is that soldiers not only obtain superior attitudes and behaviors, mastery of knowledge and skills that are reliable and soldiers who are willing but also obtain a degree that is recognized by the Directorate General of Higher Education Ministry of Research and Higher Education. The utilization of teaching staff at the Kodiklatad Polytechnic needs to be professionally managed so that the balance between the needs of the teaching staff and the interests and abilities of the educational institution is realized. This study aims to analyze the factors that influence the performance of educators at the Kodiklatad Polytechnic to achieve maximum performance. Keywords: organizational culture, work ethos, work satisfaction, educational performance.